Effect of Seed Priming with Nanosilicon on Morpho-Physiological Characterestics, Quercetin Content and Antioxidant Capacity in Calendula officinalis L. under Drought Stress Conditions - Saeedeh Rahimi; Mehrnaz Hatami; Mansour Ghorbanpour (Institue of Medicinal Plants, ACECR, 2019)
Background: Silicon is the second most structural element in the earth, which in plants, in induces physiological processes and causes resistance to biotic and abiotic stresses as well. Objective: The effect of seed priming with nanosilicon under different levels of drought stress on morphological, physiological, total phenol and flavonoid contents, quercetin levels and antioxidant capacity of the Calendula officinalis L. Method: This study was conducted as factorial experiment in a randomized complete block design (RCBD) under four levels of drought stress (25, 50, 75 and 100 %FC), and different concentrations (0, 100, 200 and 500 mg/L) of silicon nanoparticles was considered as seed priming treatment. Results: The results showed that drought stress levels and seed priming with nanosilicon at the various concentrations caused significant changes (P < 0.05) on measured traits of plant. The highest antioxidant activity of the obtained extract was observed in plants pretreated with nanosilicone at 200 mg/L under 25 %FC. Drought stress at moderate level (50 %FC) along with seed priming with nanosilicone at 100 mg /L had the highest effect on quercetin content. Furthermore, the highest and the lowest content of total flavonoid was observed in plants pretreated with silicon nanoparticles at 200 mg/L and control (without priming) under drought stress at 25 %FC, respectively. Conclusion: Applicationof nanosilicone at lower concentrations (100-200 mg/L) and drought stress at 50 %FC may improve plant physiological and metabolite indices in marigold.